The softwire virus on Orbis 1 - Haarsma, PJ. (Cambridge, Massachusettes Candlewick Press, 2006)
When twelve-year-old Johnny and his sister arrive on Orbis in a space ship of orphans, he finds he has a unique ability to communicate with computers.
Keywords: Computers -- Fiction; Orphans -- Fiction; Science fiction